2016
DOI: 10.1134/s0012496616030017
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits development of colon malignant tumors induced by 1,2-dimethylhydrazine in rats

Abstract: It has been shown that metformin dose-dependently inhibits the development of colon tumors induced by 1,2-dimethylhydrazine (DMH) in rats. The metformin effect manifested itself as a decrease in the amount and average size of tumors, increased degree of their differentiation, and reduction of invasion depth, which was more pronounced in the group of animals that received metformin at a dose of 100 mg/kg of body weight as compared with rats treated with metformin at a dose of 300 mg/kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It was proposed that metformin suppressed colonic mucosal proliferation via activation of AMPK and then the downstream suppression of the mTOR pathway ( 41 ). In other animal model, it has been shown that metformin dosedependently inhibits the development of colon tumors induced by 1,2dimethylhydrazine (DMH) in rats ( 42 , 43 ). In this way, many reports showed that metformin is effective for colorectal carcinogenesis both in vivo and in vitro .…”
Section: Metformin and Colorectal Cancermentioning
confidence: 99%
“…It was proposed that metformin suppressed colonic mucosal proliferation via activation of AMPK and then the downstream suppression of the mTOR pathway ( 41 ). In other animal model, it has been shown that metformin dosedependently inhibits the development of colon tumors induced by 1,2dimethylhydrazine (DMH) in rats ( 42 , 43 ). In this way, many reports showed that metformin is effective for colorectal carcinogenesis both in vivo and in vitro .…”
Section: Metformin and Colorectal Cancermentioning
confidence: 99%
“…Similarly, Sinagra et al have shown that longer duration of diabetes is associated with higher risk of CRC (p = 0.001) in the cohort of 741 Caucasian patients with type 2 diabetes [48]. In a large population-based study (36,270 patients with diabetes and 145,080 patients without diabetes), Lin et al showed an increased incidence of cancer, especially gastroenterological malignancies (except for esophageal cancer), in patients with diabetes. Interestingly, these authors showed that metformin significantly decreased the risk of lung and liver cancer (adjusted hazard ratio (aHR) 0.62, 95 % CI 0.45-0.85, p < 0.05, and 0.64, 95 % CI 0.49-0.83, p < 0.05, respectively), but the effectiveness of metformin in reducing the risk of CRC was less pronounced (aHR 0.74; 95 % CI 0.53-1.03, p = 0.075).…”
Section: The Incidence Of Colorectal Cancermentioning
confidence: 89%
“…In the study by Bordini et al metformin had protective properties by preventing the formation of aberrant crypt foci (ACF) and inflammatory process induced by 1,2-dimethylhydrazine (DMH) in mice [35]. In a study on rats the DMH-induced tumor formation (tumor differentiation, invasion depth) was dose dependently inhibited by metformin administration [36]. In an experimental study on metformin-treated diabetic rats with DMH-induced CRC, Jia et al showed that metformin treatment significantly inhibited formation of ACF, non-significantly (p = 0.15) reduced the total incidence of tumors, and significantly (p < 0.05) reduced the volume and number of tumors.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Metformin, a widely used drug to treat type 2 diabetes, has gained attention as a potential therapeutic option for cancer prevention and treatment 46,47 . The effects of metformin on immune cells, immune-related molecules, and the TME have been extensively studied, which has shown the impact of metformin on antitumor immune responses that influence tumor proliferation, metastasis, drug resistance, and immunotherapy outcomes.…”
Section: Metforminmentioning
confidence: 99%